2017
DOI: 10.1111/geb.12603
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of water and nutrient additions on grassland communities: A global meta‐analysis

Abstract: Aim Changes in global climate and land use are expected to alter water and nutrient availability. Various meta‐analyses and large‐scale experiments show that increasing nutrient availability is expected to decrease the diversity of ecological communities, but so far, no study has attempted to provide a global‐scale perspective of diversity responses to water manipulation. Location Global. Methods We conducted a meta‐analysis focusing on the effects of water and nutrient additions both on species richness and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
55
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 58 publications
11
55
0
1
Order By: Relevance
“…In our experiment, water was applied in the middle of the growing season (July and August); future experiments should investigate whether earlier water addition reduces plant diversity in the semi‐arid steppe we studied, as suggested by the phenology hypothesis. Note that adding N and water together removed the positive effect of water addition on species richness in our experiment, which is consistent with the finding of a recent meta‐analysis (DeMalach et al., ). One possible explanation for this result is that increased photosynthetic rate after N addition led to greater transpiration rate and more rapid depletion of water from the rooting zone and therefore reduced soil moisture (Harpole et al., ; Zavaleta et al., ), counteracting the effect of direct water addition.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our experiment, water was applied in the middle of the growing season (July and August); future experiments should investigate whether earlier water addition reduces plant diversity in the semi‐arid steppe we studied, as suggested by the phenology hypothesis. Note that adding N and water together removed the positive effect of water addition on species richness in our experiment, which is consistent with the finding of a recent meta‐analysis (DeMalach et al., ). One possible explanation for this result is that increased photosynthetic rate after N addition led to greater transpiration rate and more rapid depletion of water from the rooting zone and therefore reduced soil moisture (Harpole et al., ; Zavaleta et al., ), counteracting the effect of direct water addition.…”
Section: Discussionsupporting
confidence: 92%
“…The generality of our findings, nevertheless, remains to be assessed by future studies. We hope our work will stimulate the rapid emergence of these studies, given a number of field experiments similar to ours have already been conducted (reviewed by DeMalach et al., ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast to the rainout shelter‐induced decrease in species richness, our water addition treatment did not alter productivity, yet increased species richness. A recent meta‐analysis of 41 grassland experiments (involving a wide range of climatic and soil environments) reported no statistically significant effect of water addition on species richness (DeMalach et al., ). However, two other experiments in temperate‐mesic old‐field vegetation also found that species richness was increased by water addition (Sternberg, Brown, Masters, & Clarke, ; Stevens, Shirk, & Steiner, ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies used a wide variety of experimental designs (e.g., some with just added water, just reduced water, or both, and some also included nutrient fertilizer treatments), variable durations of treatment applications (one year vs. multi‐year), and sites from a wide range of climatic zones, soil types, and vegetation successional stages — including forest, shrubland, grassland, tundra, desert and agricultural fields. Not surprisingly, therefore, it is difficult to make meaningful comparisons of results between studies, and to draw overall conclusions (Beier et al., ; DeMalach et al., ; Hoover, Wilcox, & Young, ; Knapp et al., ; Wu et al., ).…”
Section: Introductionmentioning
confidence: 99%